Scrapie prion protein accumulation by scrapie-infected neuroblastoma cells abrogated by exposure to a prion protein antibody - Enari, Masato (The National Academy of Sciences, 2001)
Exposure of susceptible neuroblastoma N2a cells to mouse scrapie prions leads to infection, as evidenced by the continued presence of the scrapie form of the prion protein (PrP(Sc)) and infectivity after 300 or more cell doublings. We find that exposure to phosphatidylinositol-specific phospholipase C (PIPLC) or to the monoclonal anti-prion protein (PrP) antibody 6H4 not only prevents infection of susceptible N2a cells but also cures chronically scrapie-infected cultures, as judged by the long-term abrogation of PrP(Sc) accumulation after cessation of treatment. A nonpassaged, stationary infected culture rapidly loses PrP(Sc) when exposed to the antibody or PIPLC, indicating that the PrP(Sc) level is determined by steady state equilibrium between formation and degradation, and that depletion of the cellular form of PrP can interrupt the propagation of PrP(Sc). These findings encourage the belief that passive immunization may provide a therapeutic approach to prion disease.